Letter - Nottingham Trades Council Joint Dispute Committee, 8 May 1926 (Nottingham)
1926-05-08 "Letter - Nottingham Trades Council Joint Dispute Committee, 8 May 1926" [g0369001.jpg], 8 May 1926, Nottingham Trades Council Joint Dispute Committee Local Organisation